Self-Diffusion of Indium and Bismuth in Molten In0.5Bi0.5 Alloy at Different Thermodynamic State (Bangladesh Journal of Physics, 2025)
This research work focuses on the theoretical study of atomic transport properties of molten In0.5Bi0.5 alloy at different thermodynamic states. Particularly, the self-diffusion coefficients (Di) of indium (In) and bismuth (Bi) in In0.5Bi0.5 alloy are explored by utilizing Distribution Function Method, which is based on the statistical mechanical theory. Inter-ionic interactions and pair distribution function are two main components of this method. The inter-ionic interactions are modeled by using local pseudopotential known as Brettonet-Silbert model, while the pair distribution function is derived by the Ascroft –Langreth theory. The effective hard sphere diameter is the main ingredient to calculate the Di, which is deduced from the thermodynamic perturbative theory called the Linearized Weeks-Chandler-Anderson method. The calculated results indicate that the value of Di for In agrees well with the available experimental data in the low temperature region.Bangladesh Journal of Physics, Vol. 29, Issue 2, pp. 51 – 58, December 2022